Development of a Visualization System for Safety Analyst. Issue 1 (January 2014) - Paz, Alexander; Khanal, Indira; Veeramisti, Naveen; Baker, Justin; Belmonte, Loïc
The AASHTO software Safety Analyst is a state-of-the-art tool with significant capabilities and advanced analytical methods for comprehensive analysis and management of highway safety. However, this tool does not provide visualization capabilities. To address that limitation, this study proposes a visualization system for Safety Analyst that provides graphical displays, including location and color-coded information for each module. In addition, the system generates charts, which have various degrees of resolution and aggregation; tables; and a report summarizing safety performance measures. The system can use Google Maps or ESRI ArcGIS to generate the graphical displays. The advantage of using Google Maps is its simplicity; in contrast, the ArcGIS display provides additional modeling and computing capabilities of the GIS framework. All displays are very intuitive and can be customized according to user needs. Because the user can see the locations of every specific site, the displays facilitate analysis as well as the decision-making process. The visualization system interacts with Safety Analyst so that the user can access all tools and data throughout the entire modeling and analysis process.